Nurse-pharmacist collaborations for promoting medication safety among community-dwelling adults: A scoping review. (December 2022) - Ravi, Padma; Pfaff, Kathryn; Ralph, Jody; Cruz, Edward; Bellaire, Mackenzie; Fontanin, Gemma
Abstract: Background: Despite good evidence that supports improved clinical health outcomes and the cost effectiveness of nurse-pharmacist collaboration for promoting medication safety among adults in acute care settings, there is limited research in community settings. Objective: This scoping review examines, maps, and identifies gaps in the existing literature on nurse-pharmacist collaboration to augment medication safety among community-dwelling adults. Design: Setting(s): Community setting Participants: This review consists of 3, 464 participants across 23 studies Methods: We used the enhanced Arksey and O'Malley framework by Levac and colleagues. Studies from MEDLINE, CINAHL, ProQuest, Scopus, and PubMed databases implementing medication safety through nurse-pharmacist collaboration for community-dwelling adults were included. We extracted data according to country of origin, intervention, and relevance to the current review. Results: Twenty-three studies were included in this review. Nurse-pharmacist collaborations in community settings are still evolving and are in a nascent form. Five sub-themes emerged from literature review of collaboration between nurses and pharmacists in community settings for medication safety. They are creating new opportunities to address gaps in community medication safety, enabling complementary interprofessional roles in medication safety, facilitating of efficient and cost-effective measures for medication safety, diverse nature of assessments done by nurses and pharmacists, and incohesive teams due to poor collaborative practices. Conclusions: Nurse-pharmacist collaborations in community settings improved disease management, prevented adverse drug events, and reduced hospitalizations. They resulted in early identification and correction of medication safety related issues, reduced wait periods to see general practitioners, and enhanced chronic disease self-management skills among community-dwelling adults. There is a need to improve existing systems and policies through research for sustaining such collaborations especially in community settings.